1995
DOI: 10.1021/jo00114a029
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Assignment of the Pyochelins

Abstract: The synthesis of pyochelin has been much improved but gives four stereoisomers. The stereochemistry of the two naturally occurring pyochelins I and II has been assigned, based on (1) the similarity of the NMR spectra of pyochelin I methyl ester to those for 4-methylpyochelin I methyl ester, whose X-ray structure has been determined and relative stereochemistry assigned; (2) comparison of the rotation of the natural material to that of pyochelin I methyl ester synthesized from IV-methyl-L-cysteine methyl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 0 publications
7
67
0
Order By: Relevance
“…The four other diastereoisomers, NeoPchI/II and ENeoPchI/II, have so far never been isolated from any siderophore-producing strain. In the presence of a metal ion, PchII isomerizes into PchI (24,36), and NeoPchII isomerizes into NeoPchI. This suggests a metal-driven template effect giving a cis H2Љ-H4Љ relationship that is necessary for optimal ferric ion tetracoordination by the siderophore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four other diastereoisomers, NeoPchI/II and ENeoPchI/II, have so far never been isolated from any siderophore-producing strain. In the presence of a metal ion, PchII isomerizes into PchI (24,36), and NeoPchII isomerizes into NeoPchI. This suggests a metal-driven template effect giving a cis H2Љ-H4Љ relationship that is necessary for optimal ferric ion tetracoordination by the siderophore.…”
Section: Discussionmentioning
confidence: 99%
“…The purification procedure used did not separate the diastereoisomer couples. However, in the presence of a metal ion (Fe 3ϩ and Zn 2ϩ ), PchII isomerizes into PchI (35,36) by epimerization of the C2Љ carbon atom (Fig. 1).…”
Section: Binding Of Pch Diastereoisomers Tomentioning
confidence: 99%
“…Dha and salicylate were quantified at 256 and 237 nm, respectively. Pyochelin, which exists as a mixture of two interconvertible isomers, pyochelin I and pyochelin II (Rinehart et al, 1995), was quantified at 258 nm and 254 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this type of regulation, also known as siderophore-mediated signalling , perception of the siderophore can occur either at the cell surface, in the periplasm, or in the cytoplasm; examples are provided by pyoverdine-, enterobactin-and pyochelinmediated signalling in the Gram-negative bacterium Pseudomonas aeruginosa. This opportunistic human pathogen produces two siderophores, pyoverdine and pyochelin (Cox, 1980;Cox & Adams, 1985;Meyer & Abdallah, 1978;Rinehart et al, 1995), but can promote iron uptake also with a variety of heterologous siderophores of fungal and bacterial origin (Poole & McKay, 2003). Pyoverdine is perceived at the cell surface, where interaction of the ferripyoverdine complex with the outer-membrane receptor FpvA transmits a signal to the anti-sigma factor FpvR.…”
Section: Introductionmentioning
confidence: 99%
“…Pyochelin contains three chiral centres (C49, C20 and C40) and exists in solution as a mixture of two interconvertible stereoisomers ( Fig. 1): pyochelin I (49R, 20R, 40R) and pyochelin II (49R, 20S, 40R) (Ankenbauer et al, 1988;Rinehart et al, 1995) although only pyochelin I has been observed to bind ferric iron (Schlegel et al, 2004(Schlegel et al, , 2006. Upon iron chelation, pyochelin is transported back into the cell via a specific outer-membrane receptor, FptA, in conjunction with an inner-membrane permease, FptX (Ankenbauer & Quan, 1994;Ó Cuiv et al, 2004;Michel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%